Marginal leakage of polyacid-modified composite resin restorations in primary molars: an in vitro study Infiltração marginal em restaurações de resinas compostas modificadas por poliácidos, em molares decíduos: estudo in vitro - Cleide Cristina R. Martinhon; Ricardo Sousa Vieira (University of São Paulo, 2005)
The purpose of this in vitro study was to compare the marginal leakage in primary molars restored with 2 polyacid-modified composite resins (Dyract AP - Dentsply and F2000 - 3M) and a composite resin (Filtek Z250 - 3M) as control. First and second primary molars were used for preparation of cavities on the proximal surfaces, with extension of the gingival margin to the cementoenamel junction. Restorations were accomplished after total etching and application of the respective adhesive system, and were divided into groups according to the restorative system and the number of adhesive layers used. The teeth were stored in distilled water for 7 days, followed by thermocycling with 500 cycles at 5ºC - 55ºC, with one minute in each bath. Thereafter, teeth were prepared for immersion in 0.5% methylene blue solution for four hours. The teeth were sectioned in mesiodistal direction for assessment of dye penetration. According to the results of the Kruskal-Wallis test, the three restorative materials employed did not completely avoid marginal leakage at the gingival margin of primary molars. The marginal leakage of PMCR F2000 (4.06 and 3.95) displayed to be higher than the marginal leakage observed for the materials Dyract AP (2.7 and 2.55) and Filtek Z250 (2.25 and 2.43). The number of adhesive layers did not influence the degree of leakage of the three materials. O estudo in vitro avaliou a infiltração marginal em molares decíduos restaurados com três materiais resinosos: as resinas compostas modificadas por poliácidos (Dyract AP - Dentsply e F2000 - 3M) e uma resina composta (Filtek Z 250) como grupo controle. Foram utilizados primeiros e segundos molares decíduos hígidos e as cavidades foram confeccionadas nas faces proximais, estendendo-se até a junção amelo-cementária. As restaurações foram realizadas após o condicionamento ácido total e a aplicação dos sistemas adesivos divididas em grupos de acordo com o sistema restaurador e o número de camadas dos respectivos agentes adesivos, ou seja, dois grupos para cada material restaurador. Os dentes foram armazenados em água destilada durante 7 dias, em seguida a ciclagem térmica com 500 ciclos (5º C e 55º C), com um minuto em cada banho. Em seqüência os dentes foram selados para a imersão na solução de azul de metileno a 0,5%, pH 7,2, por 4 horas. A seguir, os dentes foram submetidos a cortes no sentido mésio-distal para a avaliação do grau de penetração do corante. De acordo com os resultados após a análise estatística, os três materiais testados não impediram completamente a infiltração marginal na região cervical dos molares decíduos. Com relação à infiltração marginal a RCMP F2000 (4,06 e 3,95) apresentou os maiores graus de infiltração marginal do que os outros materiais Dyract AP (2,71 e 2,55) e Filtek Z250 (2,27 e 2,43). O número de camadas dos adesivos não influiu nos graus de infiltração dos três materiais estudados.